Pengaruh Konsentrasi Pupuk Kalium Boron dan Magnesium Phospat terhadap Produksi Jagung Manis (Zea mays saccharata Sturt) - Nugroho Aji , Harlan; Sri Wahyuni , Endang (Program Studi Agroteknologi, 2021)
Under the guidance Ir. Endang Sri Wahyuni, MP as the main supervisor and the supervisor Ir. Nanik Furoidah, MP as member. This study aims to determine the effect of potassium fertilizer concentration of Boron and Magnesium Phosphate on the growth and production of sweet corn (Zea mays saccharata Sturt.). The study was conducted in August until November 2016 in the village Kertonegoro, sub Jenggawah, Jember district, in paddy fields with a height of ± 60 meters above sea level. This study was conducted using a randomized block design Complete (RAK), two factors with three replications. The first factor is the concentration of potassium fertilizer Boron (K) comprise three levels ie concentration of 0 ml/liter (K0), a concentration of 1.5 ml/liter (K1), the concentration of 3 ml/liter (K2). The second factor is the Magnesium Phosphate (P) comprises 3 levels ie concentration of 0 ml/liter (P0), the concentration of 2 ml/liter in preparation for planting, preparation for the formation of flowers, fruit, fruit ripening, 0.5 ml / liter age of 15 days, and 1 ml/liter of routine applications 7 days (P1), a concentration of 4 ml/liter in preparation for planting, preparation for the formation of flowers, fruit, ripening fruit, 1 ml/liter age of 15 days, and 2 ml/liter routine application of 7 days (P2). The results showed that the treatment concentration of fertilizer Potassium Boron and Magnesium Phosphate significantly affected all observations. Treatment of Potassium Boron concentration of 3 ml/liter (K2) gives the sweet corn production is higher than other treatments. Likewise, treatment of Magnesium Phosphate concentration of 4 ml / liter in preparation for planting, preparation for the formation of flowers, fruit, ripening fruit, 1 ml/liter age of 15 days, and 2 ml/liter of routine applications 7 days (P2) gives the highest compared to treatment more.